P325 Cow's milk protein allergy in children – clinical presentation, demographic data and family history in a study population. (June 2019) - Emmert, Vanessza; Lendvai-Emmert, Dominika; Komáromi-Szabó, Tünde; Tóth, Gergely
Abstract : Introduction: Food allergy in children is a frequent topic of clinical studies, considering the increasing number of the affected individuals and the diversity of the symptoms these children demonstrate. Cow's milk protein allergy is the most common food allergy in the paediatric population, with an estimated prevalence of 2–6% in infants. Cow's milk protein allergy can induce a variety of clinical symptoms, therefore establishing the correct diagnosis is often difficult. Beside the various clinical presentation, demographic and additional medical data of the research population and their families were also reviewed in this study. Methods: The study was conducted at the Paediatric Gastroenterology Department of the Balassa János County Hospital in Szekszárd, Hungary. The research population (n=47) included children (0–18 years) with symptoms suggesting cow's milk protein allergy. This component of our research represents the data from questionnaires filled in by the parents. The evaluation of the results was performed with SPSS statistical software. Results: 47 children were included in our study (57.4% male, mean age: 7.36 years, SD: 4.22). By reviewing the parents' medical history, 23.4% of mothers and 25.5% of fathers were diagnosed with either an atopic disease or an inflammatory bowel disease; however, examining the siblings of the affected children, 45, 7% are reported to have one of these conditions (12 children do not have any siblings). In the study population, 8.5% were born prematurely and 85.1% were born at term (6, 4% did not provide an answer). 46, 8% were exclusively breastfed in the first 6 months of life. Analysing the data about the forms of clinical presentation, 85.1% showed gastrointestinal symptoms, 63.8% demonstrated skin-related problems, 57.4% presented with respiratory manifestation and 44.7% showed behavioural problems. Conclusion: According to our results, a positive family history for atopic diseases and/or inflammatory bowel disease can increase the risk of developing cow's milk protein allergy; siblings showed a higher prevalence of food allergy when the parents were affected by the aforementioned entities. The clinical manifestations represent a wide variety of symptoms which frequently overlap, making the diagnostic process often challenging. We did not observe a significant effect of feeding (breastfeeding or formula feeding), or being premature on the risk of developing cow's milk protein allergy in children. However, it is important to emphasize the relatively small number of the study population, which is why we plan to continue the research with a larger study group.